Examining Workforce Diversity and Employee Empowerment as Drivers of Organizational Agility in Cikarang’s Manufacturing Sector - Lestari, Mutiara Retno; Rohana, Siti (Lentera Ilmu Nusantara, 2025)
This study explores the dynamics of the relationship between workforce diversity and employee empowerment on organizational agility in manufacturing companies in Cikarang. Using a quantitative approach with the purposive sampling method, the study involved 75 respondents, the majority of whom were women (71%) aged 18-27 years with a high school/vocational education background. Data analysis using Partial Least Squares (PLS) through SmartPLS revealed significant results: workforce diversity had a positive influence on organizational agility with a coefficient value of 0.148, while employee empowerment showed a stronger influence with a value of 0.691. These findings confirm that workforce diversity and employee empowerment play a role as a catalyst in transforming organizational adaptive capabilities. The research model showed a strong prediction level with an R-square of 0.726 for organizational agility. This result has strategic implications for manufacturing company management in optimizing the potential of diversity and empowerment as a transformational resource to improve organizational agility in an increasingly complex industrial era.